Expression, phosphorylation and function of the Rab‐GTPase activating protein TBC1D1 in pancreatic beta‐cells. Issue 1 (14th November 2013) - Rütti, Sabine; Arous, Caroline; Nica, Alexandra C.; Kanzaki, Makoto; Halban, Philippe A.; Bouzakri, Karim
Abstract : The Rab‐GTPase activating protein TBC1D1 is a paralog of AS160/TBC1D4. AS160/TBC1D4, a downstream effector of Akt, has been shown to play a central role in beta‐cell function and survival. The two proteins have overlapping function in insulin signalling in muscle cells. However, the expression and the potential role of TBC1D1 in beta‐cells remain unknown. Therefore, the aim of this study is to investigate whether TBC1D1 is expressed in beta‐cells and whether it plays, as AS160/TBC1D4, a role in beta‐cell function and survival. Using human and rat beta‐cells, this study shows for the first time that TBC1D1 is expressed and phosphorylated in response to glucose in these cells. Knockdown of TBC1D1 in beta‐cells resulted in increased basal and glucose‐stimulated insulin release, decreased proliferation but no change in apoptosis. Abstract : TBC1D1 is expressed in human and rat beta‐cells. TBC1D1 is phosphorylated in response to glucose. Knockdown of TBC1D1 resulted in increased basal and glucose‐stimulated insulin release. TBC1D1 is involved in beta‐cell proliferation but not in apoptosis.